2006
DOI: 10.1152/ajpheart.00669.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous progression of calcium transient-dependent beating and sarcomere destruction in apoptotic adult cardiomyocytes

Abstract: 2ϩ transients in initiation of apoptotic processes in this cell type. Simultaneously with the beating, these cells show dynamic structural alteration resulting from cytoskeletal disintegration that is quite rapid. Because of the specialized structure and extensive cytoskeleton of cardiomyocytes, we hypothesized that its degradation in so short a time would require a particularly efficient mechanism. To better understand this mechanism, we used serial video microscopy to observe ␤-adrenergic stimulation-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…Likewise, previous studies demonstrated that nifedipine inhibits rather than induces cell apoptosis of CMs [48]. Interestingly, BayK8644 only showed a tendency to increase the yield of CMs from ES cells at any differentiation stage which was more pronounced in iPS cells, suggesting that single LTCCs activity may be already near its maximum.…”
Section: Discussionsupporting
confidence: 52%
“…Likewise, previous studies demonstrated that nifedipine inhibits rather than induces cell apoptosis of CMs [48]. Interestingly, BayK8644 only showed a tendency to increase the yield of CMs from ES cells at any differentiation stage which was more pronounced in iPS cells, suggesting that single LTCCs activity may be already near its maximum.…”
Section: Discussionsupporting
confidence: 52%
“…The z-disk complex is a complicated array of proteins that also includes candidates for the stretch sensing mechanism, with α-actinin forming the backbone of the structure. Recent studies have indicated that the z-disk is among the initial targets for deterioration during isoproterenol-induced adult cardiomyocyte apoptosis [23], suggesting that z-disk integrity is a crucial indicator of cardiomyocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated an increase of reverse-mode NCX activity mediated the more [Ca 2+ ] i oscillations, thus resulting in the exacerbating reperfusion injury by low K + . It was also found that Nifedipine, a selective inhibitor of Ltype Ca 2+ channel, at the concentration of 1 μM [24,25], failed to prevent increased occurrence of [Ca 2+ ] i oscillations, and decreased cell length recovery and cell viability by reperfusion with low K + (Fig. 1B, C, and D), indicating that L-type Ca 2+ channel is not involved in the exacerbating reperfusion injury by low K + .…”
Section: Effect Of Reperfusion With Low K + On [Ca 2+ ] I Oscillationmentioning
confidence: 89%